A taxonomical study on electrophoretic pattern of blood serum protein of some fish of karakaya dam lake - Muhittin Yılmaz; Yusuf Türköz; A. Ümit Erdemli; Ercan Kalkan; Yılmaz Çİğremiş (Eurasian Journal of Veterinary Sciences)
In this study, an electrophoretic comparison of serum blood proteins of two species of fish, Capoeta trutta and Capoeia capoeta umbla, were carried out. Study was carried between june and october in 1997. Using the Random Sampling Method, 92 C. capoeta umbla and 86 C. trutta which the same age and sex were used. The iden-dification of species and subspecies were done though their metric and meristic characteristics. While 16 band pattern was observed in C. trutta, the number of protein bands lor C. capoeta umbla was 11. From the electrophoretic mobility 8 bands of species gave similar pattern, but the rest was seen to be different. As a result, we concluded that, there is a %50 similarity between C. trutta and C. capoeta umbla based on their serum blood proteins.